2014
DOI: 10.5194/bg-11-2325-2014
|View full text |Cite
|
Sign up to set email alerts
|

Methane and nitrous oxide fluxes across an elevation gradient in the tropical Peruvian Andes

Abstract: Abstract. Remote sensing and inverse modelling studies indicate that the tropics emit more CH 4 and N 2 O than predicted by bottom-up emissions inventories, suggesting that terrestrial sources are stronger or more numerous than previously thought. Tropical uplands are a potentially large and important source of CH 4 and N 2 O often overlooked by past empirical and modelling studies. To address this knowledge gap, we investigated spatial, temporal and environmental trends in soil CH 4 and N 2 O fluxes across a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
57
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(73 citation statements)
references
References 70 publications
14
57
2
Order By: Relevance
“…One potential source of concern are the negative N 2 O fluxes that we documented here. While some investigators have attributed negative fluxes to instrumental error (Cowan et al, 2014;Chapuis-Lardy et al, 2007), others have demonstrated that N 2 O consumption -particularly in wetland soils -is not an experimental artifact but occurs due to the complex effects of redox, organic carbon content, nitrate availability, and soil transport processes on denitrification (Ye and Horwath, 2016;Yang et al, 2011;Wen et al, 2016;Schlesinger, 2013;Teh et al, 2014;Chapuis-Lardy et al, 3680 Y. A. Teh et al: Seasonal variability in methane and nitrous oxide fluxes from tropical peatlands 2007).…”
Section: Western Amazonian Peatlands As Weak Atmospheric Sources Of Nmentioning
confidence: 99%
See 1 more Smart Citation
“…One potential source of concern are the negative N 2 O fluxes that we documented here. While some investigators have attributed negative fluxes to instrumental error (Cowan et al, 2014;Chapuis-Lardy et al, 2007), others have demonstrated that N 2 O consumption -particularly in wetland soils -is not an experimental artifact but occurs due to the complex effects of redox, organic carbon content, nitrate availability, and soil transport processes on denitrification (Ye and Horwath, 2016;Yang et al, 2011;Wen et al, 2016;Schlesinger, 2013;Teh et al, 2014;Chapuis-Lardy et al, 3680 Y. A. Teh et al: Seasonal variability in methane and nitrous oxide fluxes from tropical peatlands 2007).…”
Section: Western Amazonian Peatlands As Weak Atmospheric Sources Of Nmentioning
confidence: 99%
“…A. Teh et al: Seasonal variability in methane and nitrous oxide fluxes from tropical peatlands 2007). Given the low redox potential and high carbon content of these soils, it is plausible that microbial N 2 O consumption is occurring, because these types of conditions have been found to be conducive for N 2 O uptake elsewhere (Ye and Horwath, 2016;Teh et al, 2014;Yang et al, 2011).…”
Section: Western Amazonian Peatlands As Weak Atmospheric Sources Of Nmentioning
confidence: 99%
“…Although many studies have quantified the magnitude and variability of CH 4 fluxes, they often covered large spatial extents (from transects that are tens of meters to hundreds of kilometers long) which captured significant environmental gradients at those scales, but sampling locations were generally sparse (Del Grosso et al, 2000;Yu et al, 2008;Teh et al, 2014;Tian et al, 2014). The smaller-scale patterns of CH 4 fluxes within these landscapes has not been investigated as thoroughly as ecosystem scale gradients, which could be problematic if those patterns are important for estimating CH 4 fluxes Ullah and Moore, 2011;Nicolini et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, these models are only as reliable as the data used to parameterize them; as a consequence, ecosystems that are under-represented in the empirical literature or which are poorly understood may be modelled less accurately, with knock-on effects for larger-scale emissions estimates (Saikawa et al, 2013;Teh et al, 2014;Werner et al, 2007). Nitrous oxide dynamics in montane tropical ecosystems are particularly poorly understood, because past research has concentrated on N 2 O flux from lowland tierra firme forests (Saikawa et al, 2013;Teh et al, 2014;Werner et al, 2007). Montane ecosystems, however, are important components of many tropical landscapes, and account for a sizeable land area.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in continental South America, montane ecosystems (> 500 m a.s.l.) cover more than 8 % of the land surface (Eva et al, 2004), and play key roles in regional carbon (C), nitrogen (N), and greenhouse gas (GHG) dynamics (Girardin et al, 2010;Moser et al, 2011;Teh et al, 2014;Wolf et al, 2012Wolf et al, , 2011. Processbased models predict that N 2 O fluxes from these montane environments are lower than those from the lowland tropics (i.e.…”
Section: Introductionmentioning
confidence: 99%